3D modeling of branching structures for anatomical instruction. (August 2015) - Mattingly, William A.; Chariker, Julia H.; Paris, Richard; Chang, Dar-jen; Pani, John R.
Abstract: Branching tubular structures are prevalent in many different organic and synthetic settings. From trees and vegetation in nature, to vascular structures throughout human and animal biology, these structures are always candidates for new methods of graphical and visual expression. We present a modeling tool for the creation and interactive modification of these structures. Parameters such as thickness and position of branching structures can be modified, while geometric constraints ensure that the resulting mesh will have an accurate anatomical structure by not having inconsistent geometry. We apply this method to the creation of accurate representations of the different types of retinal cells in the human eye. This method allows a user to quickly produce anatomically accurate structures with low polygon counts that are suitable for rendering at interactive rates on commodity computers and mobile devices. Highlights: We develop an algorithm for easy construction of 3D branching surfaces. Constraints are defined which provide limits on useful input. Our algorithm is demonstrated constructing nerve cells of the human retina.